2019
DOI: 10.3390/md17120665
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Recombinant Phycoerythrin Modulates the Gut Microbiota of H22 Tumor-Bearing Mice

Abstract: Normal intestinal flora is widely involved in many functions of the host: nutritional metabolism; maintenance of intestinal microecological balance; regulation of intestinal endocrine function and nerve signal transduction; promotion of intestinal immune system development and maturation; inhibition of pathogenic bacteria growth and colonization, reduction of its invasion to intestinal mucosa, and so on. In recent years, more and more studies have shown that intestinal flora is closely related to the occurrenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 45 publications
0
22
0
Order By: Relevance
“…16S rRNA amplicon sequencing could be used to determine all microorganisms’ genetic composition and community function in environmental samples ( Qi et al 2019 ). In our study, the results of 16S rRNA amplicon sequencing showed that the ACE index and Chao1 index slightly increased in the MGD group compared to the NC group, but there was no significant difference.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16S rRNA amplicon sequencing could be used to determine all microorganisms’ genetic composition and community function in environmental samples ( Qi et al 2019 ). In our study, the results of 16S rRNA amplicon sequencing showed that the ACE index and Chao1 index slightly increased in the MGD group compared to the NC group, but there was no significant difference.…”
Section: Discussionmentioning
confidence: 99%
“…Candidatu_Saccharimonas has been associated with inflammatory diseases, such as gingivitis and other periodontal dysfunctions ( Cruz et al 2020 ). Alloprevotella can produce vitamin B1 and folic acid, and an increase in the abundance of Alloprevotella was associated with the improvement of intestinal disorders Seddik et al 2017 ; Qi et al 2019 ). Based on our results, the abundance of Alloprevotella in the LDG group was significantly higher than in the NC group.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of CRC has been associated with environmental and genetic factors, and has been linked with inflammatory bowel disease (IBD) and intestinal flora (11). Studies have shown that probiotics can regulate the microbiota of the intestinal tract and inhibit the progression of cancers (12). This suggests that there is a special connection between probiotics and CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, R-PE is regarded as a bioactive molecule with high value. It has been reported that R-PE has numerous biological activities, including antioxidant [9], anti-inflammatory [10], anti-aging [11], and immunomodulatory activity [12,13]. R-PE has excellent optical properties as a natural fluorescent protein [1,14].…”
Section: R-phycoerythrin (R-pementioning
confidence: 99%